The meaning of teaching and learning for professors - Madrigal Ramírez, Martha Cecilia; Ocampo Rivera, Diana Carolina; Forero Pulido, Constanza; García Aguilar, Luz Carlota (Investigación y Educación en Enfermería, 2015)
Objective. This work sought to comprehend the meaning professors from the Faculty of Nursing at Universidad de Antioquia (Colombia) assign to teaching and learning processes. Methodology. This was an educational qualitative, evaluative investigation, with ethnographic focus, conducted from 2011 to 2013. The information collection techniques were: semi-structured interview, discussion groups, y el documentary analysis. A total of 70 professors from the undergraduate Nursing program at Universidad de Antioquia participated in the study. Results. Teaching for professors means complexity, transmission of information and knowledge, cooperation with students, interaction, and transformation of reality. This does not merely depend on the vocation or on the will to carry it out; on the contrary, professors must have professional, disciplinary, and pedagogical formation. Learning for the professors means that students understood, comprehended, and were able to put the theory into practice. Also, students must commit to their own learning. Conclusion. The conceptions professors have of teaching and learning processes guide the meaning they assign to said processes and stem from their own experience, culture, professional and disciplinary formation. Assigning new meaning to teaching in nursing opens the possibility of reorienting the teaching practice. How to cite this article: Madrigal MC, Ocampo DC, Forero C, García LC. The meaning of teaching and learning for professors. Invest Educ Enferm. 2015; 33(1):